McLuhanian Perspective of Facebook - Areen Fawwaz Aldardasawi (Research in Social Sciences and Technology- OpenED Network, 2017)
As we live in the epoch of popular culture, it is very important to understand it and study its dimensions as well as their influences upon society. Technology is a very salient manifestation of popular culture that has brought substantial changes to the world. Thus, we have to be aware of the effects and the potential effects that technology may have upon us. One type of technology is Facebook which is the most popular social network website in terms of the number of members and visitors. As a virtual society, Facebook is growing more and more popular day by day. In this article, Facebook, as a technological medium, is going to be measured and explained according to Marshall McLuhan's perspective of media and technology. Therefore, we will try to explain, in McLuhan's words, how Facebook is considered a